Perancangan Sistem Absensi Ekstrakulikuler Berbasis Web Model Waterfall - Irpan Kusyadi; Atina Fahma; Dimas Nugroho; Khantaqwa Amri; Meri Hendayani; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2022)
The attendance system is important for schools in Indonesia, therefore every school applies attendance to make it easier for teachers to know which students are present. Attendance is done manually such as by writing names or making initials and calling the names of students so that they know which students are present. The attendance system at SMKN 2 Rangkas Bitung is still applied manually. Actually in the world of education there are several schools that use digital attendance and there are also schools that still use student attendance manually. With this research, we can find out how the development of attendance in a web-based attendance system can optimize student attendance at school. It was developed using the SDLC (Software Development Life Cycle) method of the Waterfallmodel. The results of this study state that the application of web-based attendance can make it easier to input attendance data and reduce the risk of data manipulation. This attendance application is also very efficient to use because students do not need to go to the supervisor to submit attendance data. The impact of developing web-based attendance is that schools become conducive and can help speed up attendance.